HUBUNGAN SENAM HAMIL TERHADAP PENURUNAN TINGKAT KECEMASAN MENGHADAPI PERSALINAN DI RS S TAHUN 2021 - Mutmainah, Vepti Triana (Ikatan Bidan Indonesia (IBI), 2022)
Background: Pregnancy exercise is very necessary for every pregnant woman, because pregnancy exercise can make the body fit and healthy, and can make pregnant women still able to carry out daily activities, so that stress due to anxiety before childbirth can be minimized. In 2019, 10 pregnant women in TR III were found, 8 of whom said they were worried about childbirth and 2 of them said they were normal because they took part in pregnancy exercises. . Research Objectives: To determine the relationship between pregnancy exercise and the reduction of anxiety levels during childbirth at the S Hospital. Research Methods: This type of research is an analytic observational study, with a case control design. The sample in this study were 36 pregnant women who previously regularly participated in pregnancy exercise, and 36 pregnant women who had never participated in pregnancy exercise. The level of anxiety of pregnant women will be measured by the Hamilton Anxiety Rating Scale. Research Results: The results of the Mann-Whitney Test showed that there were differences in the level of anxiety in the group who routinely participated in pregnancy exercise and the group that had never participated in pregnancy exercise before (P = 0.007). There is an effect of pregnancy exercise on decreasing the level of anxiety facing the delivery process in pregnant women at the S Hospital.